اَلْمُقَارَبَةُ اَلْعِرْفَانِيَّةُ فِي تَعْلِيمِيَّةِ اَلنَّحْوِ اَلْعَرَبِيِّ - خلايفة, السعيد (جامعة الوادي - University of Eloued, 2023)
مُلَخَّصٌ: يروم البحث إلي بيان دور اللّسانيات العرفانيّة في تعليميّة النّحو العربيّ على مستوى التّخطيط والإجراء؛ فأمّا على المستوى الأوّل فيتجلّى من خلال اعتماد أسلوب إدماج المعارف والوضعيّة التّعليمية المُشْكِلَة في المناهج الجديدة، وأمّا فينا يخصّ الإجراء فمن خلال طرق وآليات تعليم وتعلّم النّحو وسط التّفاعلات الصّفيّة سواء في جانبه الضّمني؛ الّذي يتعلّمه المتعلّم في مراحله الأولى على شكل وظائف لغويّة مُتَضَمَّنَةٌ في صيغ وأساليب لغويّة، يستقبلها سماعًا وقراءة وينتجها مشافهة وكتابة، لترسخ قوالب في الذهن ينسج على منوالها المتعلّم أثناء إنتاجه للغة، أو في جانبه الصّريح؛ الّذي يُقدّم على شكل معارف نظرية يسعى من خلالها المتعلّم بطريقة واعيّة إلى تعلّم قواعد وقوانين على شكل أحكام نحويّة، ليستثمرها في ضبط إنتاجه اللّغوي. Abstract: This research aims to clarify the role of gnostic linguistics in teaching Arabic grammar at the level of planning and action. As for the planning’s level, it manifests through the adoption of the method of integrating knowledge and the problematic educational situation in the new curricula. For the procedure’s level, it comes through the methods and mechanisms of teaching and learning grammar in the middle of class interactions, whether in its implicit aspect; where the learner learns in his early stages in the form of linguistic functions that are included in linguistic formulas and methods, which are received by listening and reading and produced by orally and in writing, to establish molds in the mind that weave along the learner’s pattern during the production of the language, or in his explicit form; which is presented in the form of theoretical knowledge through which the learner consciously seeks to learn rules and laws in the form of grammatical provisions, in order to invest them in controlling his linguistic production.
Article
Keywords: المقاربة العرفانية؛ اللسانيات العرفانية؛ تعليمية النحو العربي؛ النحو الصريح؛ النحو الضمني.; grammar; Explicit syntax; implicit syntaxgnostic approach; Gnostic linguistics; the didactic of Arabic